The Relationship between Mother's Attitudes about Oxytocin Massage and the Smoothness of Exclusive Breastfeeding at PMB Ernita Pekanbaru - Rika Andriyani; Risa Pitriani (Science Midwifery, 2021)
Breast milk production is stimulated by breast emptying and the principle of supply and demand applies, so that the more milk is released, the more milk is released. Oxiton massage is one way to increase and increase milk production. The research objective was to determine the relationship between mother's attitude about oxytocin massage to the smoothness of exclusive breastfeeding at PMB Ernita Pekanbaru. This research has a type of quantitative analytic research using a cross sectional research design, the study was conducted on 15 November - 15 December 2020, the sample of this study were some breastfeeding mothers whose babies were exclusively breastfed who visited PMB Ernita, the sampling technique was in this study. is a consecutive random sample, the number of samples in this study was 38 people. The results of the research from the chy square test results obtained p value 0.011 which means that there is a significant relationship between attitudes towards oxytocin massage and the smoothness of exclusive breastfeeding. The conclusion from the results of the research that has been conducted shows that from 38 respondents, of which 16 respondents have a positive attitude towards oxytocin massage, there are 22 respondents who smoothly provide exclusive breastfeeding. This shows that respondents who have a positive attitude towards oxytocin massage have a 5.8 times chance of fluently providing exclusive breastfeeding, which means that there is a significant relationship between attitudes towards oxytocin massage and the smoothness of exclusive breastfeeding carried out at PMB Ernita Pekanbaru in 2020.